Reciprocity under moral wiggle room: Is it a preference or a constraint? - Tobias Regner (Friedrich Schiller University Jena, 2016)
We analyze reciprocal behavior when moral wiggle room exists. Dana et al. (2007) show that giving in a dictator game is only partly due to distributional preferences as the giving rate drops when situational excuses for selfish behavior are provided. Our binary trust game closely follows their design. Only a preceding stage (safe outside option vs. enter the game) is added in order to introduce reciprocity. We find significantly higher rates of selfish choices in our treatments that feature moral wiggle room manipulations (between 37.5% and 45%) in comparison to the baseline (6.25%). It seems that reciprocal behavior is not only due to people liking to reciprocate but also because they feel obliged to do so.
Keywords: C72; C91; D03; D80; 330; social preferences; pro-social behavior; experiments; reciprocity; moral wiggle room; self-image concerns; trust game